Climate services needs in Kampong Speu province: Wet and dry season rice cultivation - Barlis, Angelica; Vu Huong, Ngan; Swaans, Cornelis P.M. (2022)
This info brief presents the key findings from Cambodia's climate risk workshop (CRW), specifically from the province of Kampong Speu. CRW is part of the climate service demand assessment by determining the climate and risk impact on main agricultural livelihoods, mapping the current and available farm management practices that farmers and local networks carry out to cope with climate variability in order to identify opportunities for improved practices using climate information and agro-advisory services.